2005
DOI: 10.1039/b415642k
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the concentration and isotopic composition of inputs and outputs of Pb in waters at an upland catchment in NE Scotland

Abstract: As a consequence of the accumulation of anthropogenic Pb in upland catchments, there has been much recent concern about the potential mobilisation and transport of Pb from the soils to receiving waters and also the possible harmful effects that this might have on aquatic biota. This paper presents the findings of a two-year study of Pb behaviour in an organic-rich upland catchment at Glensaugh in NE Scotland. Pb inputs to the catchment were characterised by direct measurements of Pb concentration and (206)Pb/(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 38 publications
1
26
1
Order By: Relevance
“…Given the intensity and extent of atmospheric Pb pollution, there is ongoing interest in the fate of anthropogenic Pb in forest soils throughout the temperate zone of the northern hemisphere (Siccama et al, 1980;Dö rr and Mü nnich, 1989;Dö rr et al, 1990;Friedland et al, 1992;Miller and Friedland, 1994;Johnson et al, 1995;Wang et al, 1995;Wang and Benoit, 1996;Wang and Benoit, 1997;Brännvall et al, 2001b;Semlali et al, 2001;Kaste et al, 2003;Semlali et al, 2004;Klaminder et al, 2008a,b;Kylander et al, 2008). One approach to understanding the transformations and fate of Pb in soils is to study the streams which drain their respective watersheds (LaZerte et al, 1989;Erel et al, 1990Erel et al, , 1991Patterson, 1992, 1994;Tarvainen et al, 1997;Outridge, 2000;Emmanuel and Erel, 2002;Vinogradoff et al, 2005;Graham et al, 2006;Klaminder et al, 2006;Bindler et al, 2008b;Bur et al, 2009;Landre et al, 2009). Concentrations of total dissolved Pb in natural waters may be very low (Hirao and Patterson, 1974;Erel et al, 1991), with values reported for surface waters (Field and Sherrell, 2003) and recent groundwaters (Shotyk et al, 2010) below 1 ng/L.…”
Section: Introductionmentioning
confidence: 97%
“…Given the intensity and extent of atmospheric Pb pollution, there is ongoing interest in the fate of anthropogenic Pb in forest soils throughout the temperate zone of the northern hemisphere (Siccama et al, 1980;Dö rr and Mü nnich, 1989;Dö rr et al, 1990;Friedland et al, 1992;Miller and Friedland, 1994;Johnson et al, 1995;Wang et al, 1995;Wang and Benoit, 1996;Wang and Benoit, 1997;Brännvall et al, 2001b;Semlali et al, 2001;Kaste et al, 2003;Semlali et al, 2004;Klaminder et al, 2008a,b;Kylander et al, 2008). One approach to understanding the transformations and fate of Pb in soils is to study the streams which drain their respective watersheds (LaZerte et al, 1989;Erel et al, 1990Erel et al, , 1991Patterson, 1992, 1994;Tarvainen et al, 1997;Outridge, 2000;Emmanuel and Erel, 2002;Vinogradoff et al, 2005;Graham et al, 2006;Klaminder et al, 2006;Bindler et al, 2008b;Bur et al, 2009;Landre et al, 2009). Concentrations of total dissolved Pb in natural waters may be very low (Hirao and Patterson, 1974;Erel et al, 1991), with values reported for surface waters (Field and Sherrell, 2003) and recent groundwaters (Shotyk et al, 2010) below 1 ng/L.…”
Section: Introductionmentioning
confidence: 97%
“…The sampling was carried out in conjunction with a regular 2-week sampling programme for Pb concentration and isotopic composition, . Time-series of daily precipitation, mean daily flow and mean daily temperature for ECN site at Glensaugh, together with dates of salt dilution gauging and spatial sampling survey as described in Vinogradoff et al (2005). Samples were taken from each of the six stream sites, three soil pits, precipitation, suction cup lysimeters sited close to the streams, and a number of surface water sources emerging from hillslope springs.…”
Section: Introductionmentioning
confidence: 99%
“…Dissolved lead values from the mixing experiment are very similar to the range of values measured during storm events at UNG (Table II). Dissolved lead levels in upland peatland streams have often been explained by the leaching of lead from catchment peats (e.g., Lawlor & Tipping, 2003;Vinogradoff et al, 2005). Although the mixing experiment was conducted under a worst-case scenario basis, where a large sample of contaminated peat was mixed with acidic stream water, the study establishes empirically that in-stream processing may be important in controlling dissolved lead levels in peatland streams, and can potentially account for the elevated stream water lead concentrations in these systems.…”
Section: Resultsmentioning
confidence: 99%
“…In a study of surface waters in the English Lake District by Lawlor and Tipping (2003), mean lead concentrations in three Suspended sediment concentration c mg kg −1 d mg l −1 e μg l −1 tributaries of the River Duddon, were 0.42, 0.23 and 0.70 μg l −1 . Vinogradoff et al (2005) measured dissolved lead concentrations over a two-year period at an upland stream at Glensaugh, NE Scotland. Dissolved lead concentrations ranged from 0.08 to 7.53 μg l −1 , with a mean of 0.60±0.71 μg l −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation